Mangrove distribution in Tioman and Tulai Island, Pahang, Malaysia - Saad, Shahbudin; Ahmad, Zuhairi; Khodzori, Mohd Fikri Akmal; Yusof, Muhammad Hamizan; Rani, Husaini (2012)
This study examine the mangrove cover and distribution in Tioman and Tulai Island, Pahang.Images from Landsat-7 ETM+ of Tioman and Tulai Island were analyzed using supervised classification and Principal Component Analysis (PCA). Results indicated that total of 59.895 hectares mangrove covers have been identified in both islands, with 86.49% in Tioman Island (52.7625 hectares) and 13.51% in Tulai Island (7.1325 hectares). Mangrove species have been merged into 3 major classification groups based on the spectral overlapping; Mangrove A, Mangrove Band Mangrove C. In Tioman Island, Mangrove A covers 59.91 % _(31.613 hectares) of total mangrove in the island, and Mangrove Band Mangrove C with 13.64% (7.2 hectares) and 26.43% (13.95 hectares). In Tulai Island, only Mangrove A and Mangrove B was observed. Mangrove A occupies 85.48% (6.0975 hectares) and Mangrove B covers 14.51 % (1.035 hectares). Total of 16 mangrove species was found consist of exclusive and non exclusive species; an indication of high mangrove diversity and species richness in both islands. Remote sensing and_GIS application found to be useful as the technology allowed monitoring and mapping large scale area of mangrove forest.